(3eYGde GdJfRjds - (3CMeO Hf jhSa Hf eSYhO GdaQGA GdHZhj GdMdHjs
(3ChdgG (B:s
(3bhdg (B( (3SHMGf GdPi CSQi HYHOg djdkG (B) (3hjchf SHMGf HeYfi GdJYLH CSQi HYHOg djdkG Ci SjQg cPdc SQi Hg s
(3BNQgG (B:s
(3jfJgi HCKfGA JaSjQg (B( (3SHC (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1726s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs